2019
DOI: 10.1002/cam4.2466
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐based discrimination of breast cancer cells by direct exposure to 5‐aminolevulinic acid

Abstract: Protoporphyrin IX‐fluorescence measurement is a powerful in situ approach for cancer detection after oral/topical administration of 5‐aminolevulinic acid. However, this approach has not been clinically established for breast cancer, probably due to insufficient delivery of 5‐aminolevulinic acid to the mammary glands. In the present study, we directly exposed breast cancer cells to 5‐aminolevulinic acid to assess their discrimination via protoporphyrin IX‐fluorescence. Fluorescence intensity (FI) was measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This is the first oncological study to metabolically isolate and purify GBM cells representative of infiltrative residual disease, from which candidate therapy targets are likely more clinically relevant and present a methodological approach broadly applicable for solid cancers amenable to 5-ALA-induced metabolic labeling such as melanoma or breast cancer. 16 , 17 We report on the RNAseq data acquired from these different tumor areas and validate a novel potential therapeutic target found on the invasive zone 5-ALA-positive cells.…”
mentioning
confidence: 64%
“…This is the first oncological study to metabolically isolate and purify GBM cells representative of infiltrative residual disease, from which candidate therapy targets are likely more clinically relevant and present a methodological approach broadly applicable for solid cancers amenable to 5-ALA-induced metabolic labeling such as melanoma or breast cancer. 16 , 17 We report on the RNAseq data acquired from these different tumor areas and validate a novel potential therapeutic target found on the invasive zone 5-ALA-positive cells.…”
mentioning
confidence: 64%
“…The activity of ABC superfamily G member 2 (ABCG2), which is used to discharge PpIX, also affects the PpIX FI ( Figure 1 ) [ 24 ]. Figure 2 shows the effect of Ko143, a specific inhibitor of ABCG2, on PpIX FI in human breast cancer cells and xenografts [ 26 ]. The combined exposure of cultured MCF-7 and MDA-MB 231 cancer cells to 5-ALA and Ko143 boosts PpIX-FI compared to that in cultured non-cancer MCF10A cells, suggesting an improvement in the accuracy of 5-ALA PDD ( Figure 2 A) [ 26 ].…”
Section: 5-ala Metabolic Pathwaymentioning
confidence: 99%
“…Figure 2 shows the effect of Ko143, a specific inhibitor of ABCG2, on PpIX FI in human breast cancer cells and xenografts [ 26 ]. The combined exposure of cultured MCF-7 and MDA-MB 231 cancer cells to 5-ALA and Ko143 boosts PpIX-FI compared to that in cultured non-cancer MCF10A cells, suggesting an improvement in the accuracy of 5-ALA PDD ( Figure 2 A) [ 26 ]. Increased FI attributed to the combined administration of 5-ALA and Ko143 was also observed in cancer cells acquired by fine needle aspiration in a murine tumor model ( Figure 2 B) [ 26 ].…”
Section: 5-ala Metabolic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Kobuchi et al already investigated this topic on different cancer cells and found an important variation in ABCG2 expression from one cell type to another [ 39 ]. More recently, Morita et al investigated the selective accumulation of PpIX in breast cancer cells from a tumor-bearing mouse model [ 120 ]. In a confocal fluorescence microscopy assay, they found that MCF7 and MDA-MB-231 did highly respond to 5-ALA stimulation 2 h after treatment unlike the normal epithelial MCF10A cells, supporting a selectivity for breast cancer.…”
Section: Concerning Ppix Selective Accumulation In Neoplastic Cellsmentioning
confidence: 99%